2018
DOI: 10.1111/jdi.12935
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characteristics of abnormal glucose tolerance in Japanese women in the first year after gestational diabetes mellitus

Abstract: Aims/Introduction Risk factors of type 2 diabetes mellitus in Japanese women with recent gestational diabetes mellitus are unknown. The objective of the present study was to investigate the clinical and genetic characteristics associated with postpartum abnormal glucose tolerance in Japanese women with gestational diabetes mellitus. Materials and Methods A total of 213 Japanese women with recent gestational diabetes mellitus who underwent a postpartum 2‐h oral glucose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…These findings are consistent with the premise that after proliferation, β-cells need to downregulate PAX4 to acquire a fully metabolic mature phenotype [80]. Supporting this likely role of HMG20A in islet adaptation processes during pregnancy, polymorphisms/mutations in HMG20A have also been associated with GDM as well as with postpartum abnormal glucose tolerance [11,28,113,114]. Given HMG20A function as an epigenetic modulator through regulation of the LSD1-CoREST complex, it will be of interest to determine whether long-term epigenetic modifications in offspring which are brought about during GDM may be a consequence of deregulated expression of HMG20A during pregnancy (see Section 3 and Figure 1).…”
Section: Hmg20a An Epigenetic Modulator Bridging Cns and Islets Respsupporting
confidence: 83%
“…These findings are consistent with the premise that after proliferation, β-cells need to downregulate PAX4 to acquire a fully metabolic mature phenotype [80]. Supporting this likely role of HMG20A in islet adaptation processes during pregnancy, polymorphisms/mutations in HMG20A have also been associated with GDM as well as with postpartum abnormal glucose tolerance [11,28,113,114]. Given HMG20A function as an epigenetic modulator through regulation of the LSD1-CoREST complex, it will be of interest to determine whether long-term epigenetic modifications in offspring which are brought about during GDM may be a consequence of deregulated expression of HMG20A during pregnancy (see Section 3 and Figure 1).…”
Section: Hmg20a An Epigenetic Modulator Bridging Cns and Islets Respsupporting
confidence: 83%
“…A meta‐analysis of 95,750 women with GDM found that high BMI, family history of type 2 diabetes mellitus, non‐white ethnicity, advanced maternal age, early diagnosis of GDM, high PG levels in OGTT, high HbA1c, use of insulin, multiparity, hypertension and preterm delivery were significant risk factors for progression to type 2 diabetes mellitus 10 . We 11 and others 12,13 have reported 2‐h PG in antepartum OGTT to be a risk factor for postpartum glucose abnormalities in Japanese women with GDM. Lower insulin secretion (i.e., insulinogenic index) and β‐cell function (i.e., insulin secretion‐sensitivity index 2) have also been shown to be associated with an increased risk of postpartum glucose abnormalities 11,14,15 .…”
Section: Discussionmentioning
confidence: 86%
“…We 11 and others 12,13 have reported 2-h PG in antepartum OGTT to be a risk factor for postpartum glucose abnormalities in Japanese women with GDM. Lower insulin secretion (i.e., insulinogenic index) and b-cell function (i.e., insulin secretion-sensitivity index 2) have also been shown to be associated with an increased risk of postpartum glucose abnormalities 11,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…The identification of risk factors for postpartum abnormal glucose tolerance (pAGT) could help to identify those who have a high risk of developing pAGT, and facilitate the implementation of measures such as dietary and lifestyle changes to prevent the onset of pAGT after pregnancy. A recent study analyzed the clinical and genetic characteristics of 213 Japanese women who had a recent history of GDM, and determined how these characteristics were associated with pAGT 10 . In this study cohort, the prevalence of pAGT was 28% on OGTT at a median 24.9 weeks postpartum.…”
mentioning
confidence: 99%